Tools to study and target the Siglec–sialic acid axis in cancer. (21st December 2020) - Läubli, Heinz; Kawanishi, Kunio; George Vazhappilly, Cijo; Matar, Rachel; Merheb, Maxime; Sarwar Siddiqui, Shoib
Abstract : Siglecs are widely expressed on leucocytes and bind to ubiquitously presented glycans containing sialic acids (sialoglycans). Most Siglecs carry an immunoreceptor tyrosine‐based inhibition motif (ITIM) and elicit an inhibitory intracellular signal upon ligand binding. A few Siglec receptors can, however, recruit immunoreceptor tyrosine‐based activation motif (ITAM)‐containing factors, which activate cells. The role of hypersialylation (the enhanced expression of sialoglycans) has recently been explored in cancer progression. Mechanistic studies have shown that hypersialylation on cancer cells can engage inhibitory Siglecs on the surface of immune cells and induce immunosuppression. These recent studies strongly suggest that the Siglec–sialic acid axis can act as a potential target for cancer immunotherapy. Moreover, the use of new tools and techniques is facilitating these studies. In this review, we summarise techniques used to study Siglecs, including different mouse models, monoclonal antibodies, Siglec fusion proteins, and sialoglycan arrays. Furthermore, we discuss the recent major developments in the study of Siglecs in cancer immunosuppression, tools, and techniques used in targeting the Siglec–sialic acid axis and the possibility of clinical intervention. Abstract : The Siglec–Sia axis is an important modulator of cancer immune response. There are various methods and tools used for studying and targeting this axis. The tools used for the study include diverse mouse models, Siglec–Fc fusion proteins, and sialoglycan microarray, whereas the methods used in targeting this axis are Siglec‐blocking antibodies, sialic acid mimetics, sialidase, and siRNA/shRNA/CRISPR‐Cas‐9.